Risk Factors of Early Liver Metastasis for Pancreatic Ductal Adenocarcinoma after Radical Resection. (1st June 2022) - Tong, Jingshu; Wu, Shengdong; Lu, Changjiang; Yang, Yong; Mao, Shuqi; Lu, Caide
Abstract : Background. Liver metastasis arises in many postoperative patients with PDAC, occurring in the early stage appears to lead to a very poor prognosis. Objective. We aimed to analyze the risk factors for early liver metastasis after radical resection for patients with pancreatic ductal adenocarcinoma (PDAC) and to indicate the poor prognosis of early liver metastasis. Methods. Patients who underwent pancreatectomy for PDAC at the Ningbo Medical Centre Lihuili Hospital between January 2015 and June 2021 were included. The exclusion criteria were death within 30 days after the operation, complications with other malignancies, and a positive final resection margin (R1). Liver metastasis and its occurrence time were recorded, and risk factors for early (≤6 months) liver metastasis were analyzed by logistic regression models. The prognosis of patients with early liver metastasis and different recurrence patterns was analyzed by Kaplan–Meier curves and the log-rank test. Results. From the identified cohort of 184 patients, 172 patients were included for further analysis. 55 patients developed early liver metastasis within 6 months after the operation. Univariate analysis showed that CA 125 ≥ 30 IU / ml, tumor size ≥ 4 cm, poor tumor differentiation, and portal vein/superior mesenteric vein (PV/SMV) reconstruction were risk factors, and multivariate analysis showed that poor tumor differentiation and PV/SMV reconstruction were independent risk factors for early liver metastasis. The prognosis of liver metastasis was the worst among the different recurrence patterns. Early liver metastasis indicates a poor prognosis in patients with PDAC. Conclusions. Poor differentiation and PV/SMV reconstruction are independent risk factors for early liver metastasis in patients with PDAC, and early liver metastasis indicates a poor prognosis.